Completing Digital Marketing Communication Tools for the ReviewEdu Project at Green House Technology Corporation - Nguyen, Vu Anh Dao (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Digital Marketing; 2021-2025